From Reviews to Purchase Intention: The Interplay of Customer Review, Influencer Review, and Trust in Indonesian Skincare Products - Senalasari, Widi; Maulidani, Rendi Nabin; Setiawati, Lina; Najib, Moh Farid (Journal of Marketing Innovation (JMI), 2025)
The beauty industry's rapid growth has led to a surge in local businesses, where trust is crucial for driving customer purchase intentions, especially in sensitive products like skincare. Consumers heavily rely on reviews from other users and beauty influencers. This study examines the impact of consumer and influencer reviews on the purchase intention of skincare products, with trust as a moderating variable. It is the first to test trust's moderating role in this context. Using PLS-SEM, the study analyzed 404 consumers of local skincare products in Indonesia who had seen both consumer and influencer reviews. The result of this study shows that consumer review, influencer review, and trust significantly affect the purchase intention of local skincare products in Indonesia. However, when trust is added as a mediating variable, its presence negates the influence of both customer and influencer reviews on purchase intention. This suggests that trust plays an important role, overshadowing the impact of reviews when factored into the consumer decision-making process. These insights provide valuable implications for marketers and businesses in the beauty industry, highlighting the importance of building consumer trust.